Visioning the Bus System of the Future: Stakeholders' Perspective. Issue 1 (January 2015) - Musso, Antonio; Corazza, Maria Vittoria
The European Bus System of the Future (2008–2013) was a project funded by the European Commission within the seventh Framework Program. The core of the project was to develop a new generation of bus systems to increase the attractiveness and improve the image of this transport mode. Seven European cities were selected to test the innovative measures described in this paper: Bremerhaven, Germany; Brunoy, France; Budapest, Hungary; Gothenburg, Sweden; Madrid, Spain; Rome; and Rouen, France. The results served as a basis to develop the transferability exercise, that is, the assessment of drivers and barriers that might endorse or hinder the transferability of the measures to other cities. The transferability exercise required a specific method to define what was transferable from the experience of the seven cities (the use cases) and "to which contexts, " according to the panel of stakeholders who took part in the transferability exercise. The paper describes how the method was applied and the outcomes of the transferability exercise, which simulated the transferability of the experience of the seven use cases to a cluster of target cities across Europe. The resulting key factors for transferring (or not) the innovations and for developing a new generation of buses far beyond Europe's borders are reported.